Avaliação da reparação de feridas cirúrgicas em coelhos, tratadas ou não com plasma rico em plaquetas autólogo em gel - Santos, Eliane Szücs dos (2013)
In order to evaluate the effect of platelet-rich plasma (PRP) autologous gel on wound healing in experimental models in vivo, wounds were induced on the back of rabbits with the aid of a punch 8mm, using the right side as the control (A) treated with 0.9% NaCl and the left (B) treated with autologous PRP gel. Lesions were evaluated for a period of 17 days. It was used six white New Zealand rabbits (n=3 males and n=3 females), adult, weighing 3.0 ± 1.0 kg. On days 0, 3, 7, 10, 14 and 17, the animals were evaluated for weight and behavior, and the wounds were evaluated morphologically and morphometrically. On the 17th day the wounds was biopsied for histopathological evaluation. The morphology of the wounds evaluated statistically by the methods of Mauchly and contrasts by Sidak method and t-test. Macroscopically was evident early healing of the wound treated with autologous PRP gel in relation to the control, which was also confirmed in the histological analysis. It was concluded that PRP is effective and accelerates the healing process when applied in short intervals and in series, confirming the therapeutic potential for cutaneous lesions. It may also be an alternative treatment of wounds.